Testovací metody pro hodnocení radiačních efektů v přesných analogových a signálově smíšených obvodech pro aplikace v kosmické elektronice - Hofman, Jiří (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2019)
The traditional radiation testing of space electronics has been used for more than fifty years to support the radiation hardness assurance. Its typical goal is to ensure reliable operation of the spacecraft in the harsh environment of space. This PhD research looks into the radiation testing from a different perspective; the goal is to develop radiation testing methods that are focused not only on the reliability of the components but also on a continuous radiation-induced degradation of their performance. Such data are crucial for the understanding of the impact of radiation on the measurement uncertainty of data acquisition systems onboard research space missions.

The traditional radiation testing of space electronics has been used for more than fifty years to support the radiation hardness assurance. Its typical goal is to ensure reliable operation of the spacecraft in the harsh environment of space. This PhD research looks into the radiation testing from a different perspective; the goal is to develop radiation testing methods that are focused not only on the reliability of the components but also on a continuous radiation-induced degradation of their performance. Such data are crucial for the understanding of the impact of radiation on the measurement uncertainty of data acquisition systems onboard research space missions.
Test Methods for Evaluation of Radiation Effects in High Precision Analog and Mixed-Signal Devices for Space Applications
Keywords: Analogue to digital converter; automated test equipment; bias; calibration; CubeSat; data acquisition system; delta-sigma modulation; detector; dosimeter; dosimetry; in- orbit testing; in-situ testing; ionising chamber; measurement; measurement uncertainty; metrology; modelling; multimeter; nanosat; NewSpace; RADFET; radiation; sensor; single event effects; source-measurement unit; space environment; temperature; temperature coefficient; temperature drift; test instrumentation; test software; testing; thermometer; total ionising dose; vacuum; voltage reference.; Analogue to digital converter; automated test equipment; bias; calibration; CubeSat; data acquisition system; delta-sigma modulation; detector; dosimeter; dosimetry; in- orbit testing; in-situ testing; ionising chamber; measurement; measurement uncertainty; metrology; modelling; multimeter; nanosat; NewSpace; RADFET; radiation; sensor; single event effects; source-measurement unit; space environment; temperature; temperature coefficient; temperature drift; test instrumentation; test software; testing; thermometer; total ionising dose; vacuum; voltage reference.